Identification of a Five-Gene Prognostic Model and Its Potential Drug Repurposing in Colorectal Cancer Based on TCGA, GTEx and GEO Databases - Yang, Feng; Cai, Shaoyi; Ling, Li; Zhang, Haiji; Tao, Liang; Wang, Qin (Frontiers in Genetics, 2021)
Colorectal cancer (CRC) is one of the major causes of cancer death worldwide. What’s worse, many CRC patients are still diagnosed at the advantage stage and the five-year survival rate is only ~30%. Thus, effective prognostic markers of CRC are urgently needed. To address this issue, we performed a detailed bioinformatics analysis based on the Cancer Genome Atlas (TCGA), Genotype-Tissue Expression (GTEx) and Gene Expression Omnibus (GEO) databases to identify prognostic biomarkers for CRC, which in turn help to explore the potential drug-repurposing. We identified five hub genes (PGM2, PODXL, RHNO1, SCD and SEPHS1), which had good performance in survival prediction and might involve in CRC through three key pathways (‘Cell cycle’, ‘Purine metabolism’ and ‘Spliceosome’ KEGG pathways) identified by KEGG pathway enrichment analysis. What’s more, we performed co-expression analysis between five hub genes and transcription factors to explore the upstream regulatory. Furthermore, we screened the potential drug-repurposing for the five hub genes in CRC according to the Binding DB and ZINC15 databases. Taking together, we constructed a five-gene signature to predict overall survival of CRC and found the potential drug-repurposing, which may improve the outcome of CRC in the future.